Genomic duplication in the 19q13.42 imprinted region identified as a new genetic cause of intrauterine growth restriction. Issue 6 (17th October 2018) - Petre, Graciane; Lorès, Patrick; Sartelet, Hervé; Truffot, Aurélie; Poreau, Brice; Brandeis, Sandrine; Martinez, Guillaume; Satre, Véronique; Harbuz, Radu; Ray, Pierre F.; Amblard, Florence; Devillard, Françoise; et al.
Abstract : We report findings from a male fetus of 26 weeks' gestational age with severe isolated intrauterine growth restriction (IUGR). Chromosomal microarray analysis (CMA) on amniotic fluid cells revealed a 1.06‐Mb duplication in 19q13.42 inherited from the healthy father. This duplication contains 34 genes including ZNF331, a gene encoding a zinc‐finger protein specifically imprinted (paternally expressed) in the placenta. Study of the ZNF331 promoter by methylation‐specific‐multiplex ligation‐dependent probe amplification showed that the duplicated allele was not methylated in the fetus unlike in the father's genome, suggesting both copies of the ZNF331 gene are expressed in the fetus. The anti‐ZNF331 immunohistochemical analysis confirmed that ZNF331 was expressed at higher levels in renal and placental tissues from this fetus compared to controls. Interestingly, ZNF331 expression levels in the placenta have previously been reported to inversely correlate with fetal growth parameters. The original observation presented in this report showed that duplication of ZNF331 could be a novel genetic cause of isolated IUGR and underlines the usefulness of CMA to investigate the genetic causes of isolated severe IUGR. Abstract :